(3GdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3ESeGYjd Hf ehSi Hf YHO Gddg s)
(3ChdgG (B:s
(3PgHJ GdYRi adG YRi HYO Gdjhe GHf YSGcQ Yf bJGOI eQSdkG s
(3BNQgG (B:s
(3bGd eDdag aQZJ fe JGdjag jhe GdCKfjf GdeHGQc KGef YTQ TgQ QHjY GdChd SfI SHY hJSYeGFI ef GdgLQg s
(3HgG fXGe GdJYbjHIs
(3hbO cJH QCS GdMOjK hGdQehR HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdMOjK h GdeUWdMs